The Role of Interaction Quality and Switching Costs in Premium Banking Services - Laksamana, Patria; Wong, David; Kingshott, Russel; Muchtar, Fatimah (Emerald Group Publishing Limited, 2013)
Purpose - This paper re-examines the commitment-trust model (Morgan and Hunt, 1994) in the context of premium banking services. Inline with Toncar and Munch (2010) we seek to develop an extension to the model because of the need to encapsulate contextual variables that constrain the link between the core relationship marketing constructs of trust and commitment.Design/methodology/approach - A series of qualitative interviews were administered with bank relationship managers and premium banking customers. This enabled the concurrent consideration of both bank and customer views that helped to establish converging lines of thought within the bank-customer relationship.Findings - Our findings provided evidence of the commitment-trust link, and in particular continuance-based commitment, within the context of premium banking relationships. By triangulating our findings with current thinking in relationship marketing literature we present propositions for interaction quality and switching costs to be salient moderators between trust and commitment in this premium segment. A conceptual model that outlines the interplay between these four constructs is offered.Originality/value - Few have examined the commitment-trust link in light of moderator variables within retail banking services, and this research is the first to examine this specifically in the premium banking segment where customers are likely to be financially savvier and less knowledge dependent. This research therefore takes the first step in developing an extension to the commitment-trust model for this segment, and forms the basis for further empirical research to examine the specific impact of interaction quality and switching costs, particularly in relation to continuance-based commitment.